Konsep Filosofis Budaya Reba pada Tradisi Suku Bajawa dalam Terang Dialogis Martin Buber - Alexandro Yulianto Mawo Radho (Universitas Insan Budi Utomo, 2024)
This research paper focuses on discovering the philosophical values ​​that are formed in the Reba Cultural Unity of the Bajawa Tribe, Flores-East Nusa Tenggara. Reba culture is an expression of gratitude for the harvest and the gift of life received during the year. This traditional ceremony is also an opportunity for reconciliation or repairing deep relationships between humans and God, humans and each other, as well as humans with their ancestors and nature. Reba is held once a year according to the traditional Bajawa calendar. This culture creates a unique relationally. This research uses library research and qualitative research through interviews. The author tries to find the philosophical meaning of the Reba culture of the Bajawa tribe using Martin Buber's dialogic perspective. The Reba ceremony carried out by the Bajawa tribe actually has a dialogic relationship; I-It and I-Thou as intended in Martin Buber's philosophy. Humans relate to each other to achieve certain goals and create existential relationships from the existence of each other. Humans will achieve meaning in their lives when there is a deep I-thou-fellow relationship that is not considered inferior but creates respect and concern for others.